THE ECONOMIC EFFICIENCY OF DIGITALIZATION IN TRANSPORTATION: A SYSTEMATIC REVIEW OF APPLICATIONS AND IMPACTS - Shahzodahon Ghulomjonova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract Digitalization in transportation, encompassing technologies such as AI, IoT, blockchain, and big data analytics, has emerged as a pivotal driver for enhancing economic efficiency amid global challenges like cost pressures, supply chain disruptions, and sustainability demands. This study conducts a systematic literature review (SLR) following PRISMA guidelines to evaluate the economic impacts of digitalization in transport sectors, focusing on cost reductions, productivity gains, and sustainability synergies. Drawing from Scopus-indexed articles published between 2020 and 2025, the review analyzes 15 key studies. Results indicate that digital technologies can yield up to 20-50% cost savings in logistics through optimized routing and predictive maintenance, while also reducing carbon emissions by 10-30% via efficient fleet management. However, implementation barriers, including high initial investments and regional disparities, moderate these benefits. The discussion highlights policy implications for fostering digital adoption to achieve sustainable economic growth in transportation.